Cross‐national mentoring ngos in transition societies: Field research and developments in Bulgaria - Bogdanova, Mariana (Journal of Business Economics and Management, 2008)
Non‐governmental organizations (NGOs) in societies undergoing socio‐economic transition are widely regarded as central to building a civil society that encourages democracy. At the moment, the Bulgarian civil society depends greatly on foreign funding whilst NGOs are unable to empower their beneficiaries in decision‐making. Given this reality, are cross‐national NGO partnerships able to strengthen organisations? What kinds of support are on offer, what kinds of (inter) dependency relations occur and to what extent do NGOs model their management practices on their mentor and with what results? This paper sets out to situate these questions in the context of a proposed theoretical construct, organizational mentoring, which occurs where national or local organisations have access to and support of well‐established NGOs abroad. The model is constructed on the findings of a qualitative case study conducted in Bulgaria on the development of a Bulgarian NGO and its relationship with a UK NGO. This is preceded by a discussion on selected literature reflecting the meaning of transition, change in societal values and organizational practices in Eastern Europe, and the development of voluntary sector organizations in transforming countries. The theoretical model proposed here is relevant in providing a systematic discussion on organizational change towards a more enlightened engagement between civil society organizations in cross‐national partnerships. Such discussion has implications for the development of hybrid forms of coexistence between Eastern and Western European partners reflected in their interdependent organizational practices.First published online: 14 Oct 2010